العامل الايديولوجي والقومي للمحافظين الجدد بين الثابت والمتغير _إدارة ترامب إنموذجاً (قضايا سياسية, 2022)
Despite the rootedness of the idea of ​​nationalism in Western political thought and the great interest in it by Western thinkers, it has witnessed many developments and changes as a result of the quest of many Western countries, foremost of which is the United States, to achieve its higher political interests and national principles represented in the practical application of the pragmatic philosophy whose principles were laid down by the American philosopher John Dewey. This study seeks to verify the hypothesis that the influence of the ideological and national factors on the political thinking of the neo-conservatives and its reflection on their political behavior, especially during the period in which Donald Trump assumed the presidency of the United States (2017-2021). The study aims to identify the nature of the political and ideological ideas of the neo-conservatives, and to address the impact of the religious factor on the thought of the neo-conservatives, in addition to clarifying the nature of the political ideas and beliefs of US President Trump. The results of the study showed that the political thought of the neo-conservatives had undergone clear transformations during the tenure of President Trump, who represented the hard-line conservative movement. These transformations have emerged in the approach of American behavior in international interaction, as the concept of nationalism and the quest for economic realization dominated the internal and external behavior pattern of American policy, which led to military intervention in Afghanistan, Iraq, and other countries, it sought to adopt the method of spreading democracy and overthrowing the old regimes in different ways.